The Celts in Portugal - (:unkn) unknown (My University, 2005)
The Iberian Peninsula was famous in antiquity for its richness in metal ores, because of which it became a well-known region whose silver, gold, tin, and copper were highly sought after by Mediterranean and other European peoples. Its geographic location gave it the reputation of being at the end of the world. In a sense, it actually was the end of the known world. Some of the legends of Hercules are described as taking place there. Ancient authors refer to it quite often, thus we know a lot about the area, the events that took place there and the different peoples who inhabited it, the Greeks, the Phoenicians and the Celts among them. My argument here will follow a precise short scheme in an attempt to synthesize the existing evidence on this fascinating subject. The following sources of evidence will be discussed in this paper: the reports of ancient authors, the archaeological data, the monuments and funerary inscriptions, the linguistic documents, and artistic representations including Celtic symbolism, ideals and concepts.
Keywords: Finisterra; Periplus; gossan; stamped pottery; Cultura Castreja; Cultura dos Verrões; Pedra Formosamonuments